2013
DOI: 10.1152/ajplung.00423.2012
|View full text |Cite
|
Sign up to set email alerts
|

The anti-asthma herbal medicine ASHMI acutely inhibits airway smooth muscle contraction via prostaglandin E2activation of EP2/EP4receptors

Abstract: Our previous studies have shown that the anti-asthma traditional Chinese medicine herbal formula ASHMI (anti-asthma simplified herbal medicine intervention) inhibits acetylcholine-induced contractions of tracheal rings from ovalbumin-sensitized and naive mice in a ␤-adrenoceptor-independent manner. We sought to determine whether acute in vivo ASHMI administration inhibits airway hyperreactivity (AHR) in a murine model of allergic asthma and acetylcholine-induced tracheal ring constriction ex vivo and to elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In the current report, the suppressive effect of the EP4 agonist could be further enhanced by the EP2 agonist in accordance with other systems. 62,63 Although the EP3 agonist had a stimulatory effect on BMcMCs, inhibition by EP2 and especially by EP4 seemed to prevail and dictate the overall effect of PGE 2 . 64 Contrary to some literature, which detected enhanced secretory competence of MCs by PGE 2 (mostly via EP3) in vitro, the majority of previous reports and our current findings demonstrate a suppressive action of PGE 2 .…”
Section: Ep4 Is Highly Expressed In Human Skin Mcs With Comparable Imentioning
confidence: 99%
“…In the current report, the suppressive effect of the EP4 agonist could be further enhanced by the EP2 agonist in accordance with other systems. 62,63 Although the EP3 agonist had a stimulatory effect on BMcMCs, inhibition by EP2 and especially by EP4 seemed to prevail and dictate the overall effect of PGE 2 . 64 Contrary to some literature, which detected enhanced secretory competence of MCs by PGE 2 (mostly via EP3) in vitro, the majority of previous reports and our current findings demonstrate a suppressive action of PGE 2 .…”
Section: Ep4 Is Highly Expressed In Human Skin Mcs With Comparable Imentioning
confidence: 99%
“…For example, anti-asthma herbal medicine made from extracts from Ganoderma lucidum , Glycyrrhiza uralensis and Sophora flavescens alleviates bronchoconstriction in an animal model whilst restoring cytokines balance, contributing to longer lasting anti-asthma benefit after treatment [ 66 ]. The therapeutic effect only emanates from the synergistic effect of chemical components of the three herbal ingredients [ 67 , 68 ]. The adoption of Good Manufacturing Practises has allowed the increased use of plant-based medicines and many are now undergoing clinical trial for FDA approval [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation, assessed as isoprostane levels, is found to be markedly increased in acute asthma, and falls with resolution of the exacerbation [48]. Srivastava et al found the anti-asthma herbal medicine ASHMI inhibited airway smooth muscle contraction via prostaglandin E2 activation of EP2/EP4 receptors [49]. PGD 2 can accelerate T H 2 type (IL-4 and IL-5) inflammation by induction of macrophage-derived chemokines [50].…”
Section: Discussionmentioning
confidence: 99%